2022
DOI: 10.3390/bioengineering9060250
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Biocompatible Adhesives for the Effective Stabilisation, Repair and Regeneration of Bone

Abstract: Bone defects and complex fractures present significant challenges for orthopaedic surgeons. Current surgical procedures involve the reconstruction and mechanical stabilisation of complex fractures using metal hardware (i.e., wires, plates and screws). However, these procedures often result in poor healing. An injectable, biocompatible, biodegradable bone adhesive that could glue bone fragments back together would present a highly attractive solution. A bone adhesive that meets the many clinical requirements fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…In our study, plasma surface treatment was used as a modified method for establishing stable HSEs by generating polar groups on the tissue surface (Jacobs et al, 2012; Wieland et al, 2020). The formation of covalent bonds between the amino groups of fibrous protein with carboxylic acid groups on an oxygenated surface is achieved by plasma treatment (Tzagiollari et al, 2022). Additionally, functionalities centered on oxygen and nitrogen are generated on the base surfaces, resulting in increased hydrogen bond formation with the polar groups in the hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, plasma surface treatment was used as a modified method for establishing stable HSEs by generating polar groups on the tissue surface (Jacobs et al, 2012; Wieland et al, 2020). The formation of covalent bonds between the amino groups of fibrous protein with carboxylic acid groups on an oxygenated surface is achieved by plasma treatment (Tzagiollari et al, 2022). Additionally, functionalities centered on oxygen and nitrogen are generated on the base surfaces, resulting in increased hydrogen bond formation with the polar groups in the hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…[5]. Moreover, medical factors such as age, gender, lifestyle, and preexisting conditions influence the risk of fracture and complications arising during the recuperation process [6][7][8]. A recent study on the global burden of morbidity suggested that approximately 178 million people (53% male and 47% female) worldwide suffered from bone fractures in 2019, exemplifying an increase of roughly 34% since 1990 [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, these too suffer from limitations; metallic materials are non‐degradable and can cause chronic inflammation; [ 10 ] bioceramics have the drawbacks of brittleness, lack of processability, and poor mechanical properties; [ 11 ] polymeric materials, especially synthetic materials, may release toxic moieties during degradation. [ 6,12 ] Most importantly, many pre‐existing materials for bone regeneration lack shape‐adaptive and adhesive properties, which are required to repair irregular bone defects and multiple fragments in complex bone fractures. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,12 ] Most importantly, many pre‐existing materials for bone regeneration lack shape‐adaptive and adhesive properties, which are required to repair irregular bone defects and multiple fragments in complex bone fractures. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%